2016
DOI: 10.17233/se.43089
|View full text |Cite
|
Sign up to set email alerts
|

Yenilenebilir Enerji Tüketimi İle Ekonomik Büyüme Arasındaki İlişki: G-20 Ülkeleri

Abstract: The main purpose of this study is to determine the effects of an increase in real income per capita on renewable energy consumption per capita during 1992 and 2010. The panel cointegration analysis results of this study points out the existence of a long run relationship among renewable energy consumption and economic growth for G-20 countries. Afterwards the direction of this long run relationship is estimated by panel model estimators. In this regard it is found that 1% increase in real GDP per capita causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 44 publications
0
2
0
3
Order By: Relevance
“…In their analysis, Bakirtas et al [44,45] found a long-run cointegration between renewable energy and economic growth and a causality from economic growth to renewable energy.…”
Section: Methodsmentioning
confidence: 99%
“…In their analysis, Bakirtas et al [44,45] found a long-run cointegration between renewable energy and economic growth and a causality from economic growth to renewable energy.…”
Section: Methodsmentioning
confidence: 99%
“…Caruso et al [38] reached similar findings for selected EU countries. However, Menyah et al [39], Ocal and Aslan [40], and Bakirtas et al [41] reached a significant causality from economic growth to renewable energy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ekonomik gelişme ve yenilenebilir enerji tüketimi arasında uzun dönemde pozitif yönlü bir ilişki olduğu ortaya çıkmıştır. Bakırtaş ve Çetin (2016Bakırtaş ve Çetin ( ), 1992Bakırtaş ve Çetin ( -2010 dönemi için G-20 ülkeleri üzerinden yaptıkları çalışmalarında ekonomik büyümenin uzun dönemde yenilenebilir enerji tüketimini pozitif etkilediğini saptamışlardır.…”
Section: International Journal Of Economic and Administrative Studiesunclassified